Practical synthesis of aryl-2-methyl-3-butyn-2-ols from aryl bromides via conventional and decarboxylative copper-free Sonogashira coupling reactions - Caporale, Andrea; Tartaggia, Stefano; Castellin, Andrea; De Lucchi, Ottorino (Beilstein Journal of Organic Chemistry, 2014)
Two efficient protocols for the palladium-catalyzed synthesis of aryl-2-methyl-3-butyn-2-ols from aryl bromides in the absence of copper were developed. A simple catalytic system consisting of Pd(OAc)2 and P(p-tol)3 using DBU as the base and THF as the solvent was found to be highly effective for the coupling reaction of 2-methyl-3-butyn-2-ol (4) with a wide range of aryl bromides in good to excellent yields. Analogously, the synthesis of aryl-2-methyl-3-butyn-2-ols was performed also through the decarboxylative coupling reaction of 4-hydroxy-4-methyl-2-pentynoic acid with aryl bromides, using a catalyst containing Pd(OAc)2 in combination with SPhos or XPhos in the presence of tetra-n-butylammonium fluoride (TBAF) as the base and THF as the solvent. Therefore, new efficient approaches to the synthesis of terminal acetylenes from widely available aryl bromides rather than expensive iodides and using 4 or propiolic acid rather than TMS-acetylene as inexpensive alkyne sources are described.
Keywords: alkynes; decarboxylative couplings; Erlotinib; palladium; propiolic acid